Pricing model for eliminating productivity concerns of outsourced software maintenance services. (1st January 2012) - Kundu, Jagadish; Mukherjee, Abhik
Like light, which has a wave-particle dual nature, IT entities also exhibit duality in terms of being a product as well as service. But, unlike daylight, IT entities come at a price. The concepts of industrial engineering have to be considered with a service-sector orientation to arrive at an effective pricing strategy for IT entities. With the proliferation of outsourcing of IT to offshore locations, the concerns regarding the productivity of the personnel are increasing. The benefits of offshoring are partly neutralised by the lesser productivity and higher management overhead. This paper recommends a new pricing model which leverages Weibull distribution modelling of the software maintenance service requests. We have applied the predetermined prices suggested by the model on live projects, and observe that it has eliminated the productivity concerns and reduced the management overhead significantly.